Chromosomal abnormalities in liver cell dysplasia detected by comparative genomic hybridisation. Issue 4 (1st August 2001) - Marchio, A; Terris, B; Meddeb, M; Pineau, P; Duverger, A; Tiollais, P; Bernheim, A; Dejean, A
Abstract : Background/Aim —The pathogenetic relation between liver cell dysplasia and hepatocellular carcinoma (HCC) is poorly understood. The aim of this study was to determine whether there is a genetic link between liver cell dysplasia and HCC that could support the role of dysplasia as a tumour precursor lesion. Methods —Microdissection from paraffin wax embedded sections and degenerate oligonucleotide primed polymerase chain reaction (DOP-PCR) were combined to analyse chromosomal imbalances by comparative genomic hybridisation (CGH) in nine HCCs and nodules containing liver cell dysplasia and cirrhosis adjacent to the tumours. Seven cases of large cell changes (LCC) and three cases of small cell changes (SCC) were analysed. The genetic abnormalities detected in liver cell dysplasia were then compared with those present in the corresponding HCC. Results —No abnormalities were detected in LCC and cirrhotic nodules, arguing against the preneoplasic nature of these cell foci. In contrast, a subset of chromosomal alterations present in HCCs was found in the adjacent SCC. Conclusions —These findings support the preneoplastic status of SCC in human hepatocarcinogenesis.